Anxiety: A Source of Test Bias? - Parviz Ajideh; Massoud Yaghoubi-Notash; Abdolreza Khalili (Language Center of Islamic Institute of Uluwiyah (IAI Uluwiyah) Mojokerto Indonesia, 2017)
The present study investigated the foreign language classroom anxiety and test anxiety as sources of bias in English vocabulary and grammar tests. First, 158 intermediate EFL learners were selected as the participants. Second, the participants respectively took the Foreign Language Classroom Anxiety Scale (Horwitz, Horwitz, & Cope, 1986), Test Anxiety Scale (In’nami, 2006), the vocabulary test of the study, and the grammar test of the study in a 2-week period. The standard multiple regression was employed for data analysis. The results revealed that, classroom anxiety and test anxiety had significant negative correlations with the vocabulary and grammar test results.